2006
DOI: 10.1158/0008-5472.can-05-3792
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Endogenous Human Promyelocytic Leukemia Isoforms

Abstract: Promyelocytic leukemia (PML) has been implicated in a variety of functions, including control of TP53 function and modulation of cellular senescence. Sumolated PML is the organizer of mature PML bodies, recruiting a variety of proteins onto these nuclear domains. The PML gene is predicted to encode a variety of protein isoforms. Overexpression of only one of them, PML-IV, promotes senescence in human diploid fibroblasts, whereas PML-III was proposed to specifically interact with the centrosome. We show that al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
177
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(197 citation statements)
references
References 57 publications
20
177
0
Order By: Relevance
“…We report here that in U937 cells the expression level of PML-I is mainly elevated in activated cells. This fits with recent a report demonstrating that PML-I protein is much more abundant in macrophages (59). It was recently reported that PML-I forms a complex with AML1, targets it into nuclear bodies, enhances AML1-mediated transcription, and stimulates differentiation of myeloid cells (37).…”
Section: Discussionsupporting
confidence: 92%
“…We report here that in U937 cells the expression level of PML-I is mainly elevated in activated cells. This fits with recent a report demonstrating that PML-I protein is much more abundant in macrophages (59). It was recently reported that PML-I forms a complex with AML1, targets it into nuclear bodies, enhances AML1-mediated transcription, and stimulates differentiation of myeloid cells (37).…”
Section: Discussionsupporting
confidence: 92%
“…Although our results indicate a general affinity of E1B-55K for human PML-IV/V as well as a specific subset of rat PML, which may represent the rat orthologs of these isoforms, it seems premature to draw a final conclusion of the exchangeability of results obtained in either of these two systems as no data are available concerning the expression of PML in rats (Supplementary Figure 1). In this context, recent data concerning the organization of the murine pml locus underline the possibility of species-specific PML expression with partial homologous nevertheless considerably differing PML isoforms (Goddard et al, 1995;Condemine et al, 2006). Ongoing studies are dedicated to reveal the molecular background of the isoform-specific E1B-55K PML interaction during infection (Figure 3) as E1B-55K per se only seems to be capable of binding to PML-IV/V (Figure 2).…”
Section: Discussionmentioning
confidence: 97%
“…As PML expression is frequently deregulated in human tumour cell lines and/ or during oncogenesis Gurrieri et al, 2004;Scaglioni et al, 2006), we analysed several human tumour and pseudoprimary cell lines for endogenous PML expression (Supplementary Figure 1). Consequently, we decided to use human hepatocytic cells (HepaRG) (Gripon et al, 2002;Cerec et al, 2007), as they express PML in the well-defined physiological amounts (Condemine et al, 2006) and represent a suitable system to analyse endogenously PML components during viral infection Lukashchuk and Everett, 2010). Cells were infected with wild-type virus (H5pg4100), E1B-55K null mutant H5pm4149 (Kindsmu¨ller et al, 2009) or previously described H5pm4102/H5pm4101 virus harbouring mutations within the SCM (K104R)/NES (L83/87/91A) of E1B-55K (Kindsmu¨ller et al, 2007).…”
Section: Sumoylation Of E1b-55k Regulates Pml Interaction P Wimmer Et Almentioning
confidence: 99%
“…This antibody was raised against amino acids 1-581 of mouse PML, which is composed of 808 residues and is approximately 90-106 kDa 27 corresponding to mouse isoform 1 (NM 08884), the ortholog of the human isoform I. 28 In the MEF lysates, this antibody recognized the expected B90-106 kDa band and an additional major PML isoform, at B50 kDa. Unlike the well-studied human PML isoforms, however, the identity of additional mouse isoforms is less clear.…”
Section: E6ap Decreases Pml Protein Levelsmentioning
confidence: 99%